Impact of polyphenolic components from mulberry on apoptosis of vascular smooth muscle cells. (19th February 2015) - Chan, Kuei‐Chuan; Ho, Hsieh‐Hsun; Lin, Ming‐Cheng; Huang, Chien‐Ning; Huang, Hui‐Pei; Wang, Chau‐Jong
Abstract: BACKGROUND: Previous studies have shown that mulberry polyphenolic compounds have an anti‐atherosclerotic effect in rabbits. Apoptosis of vascular smooth muscle cells (VSMCs) is the key determinant of the number of VSMCs in remodeling. To examine the effect of mulberry polyphenol extracts (MPEs) on the apoptosis of VSMCs and thus the prevention of atherosclerosis, this study investigated the ability of MPEs to induce apoptosis in vitro and the underlying mechanism. RESULTS: It was found that MPEs initially activated JNK/p38 and p53, which in turn activated both Fas‐ligand and mitochondrial pathways, thereby causing mitochondrial translocation of Bax and a reduction in Bcl‐2. This then triggered the cleavage of procaspases, finally resulting in apoptosis of VSMCs. CONCLUSION: This study shows that MPEs may suppress atherosclerosis through stimulating apoptosis of VSMCs via activating JNK/p38 and p53 signaling. © 2015 Society of Chemical Industry